2020
DOI: 10.1002/ctm2.226
|View full text |Cite
|
Sign up to set email alerts
|

Mannose synergizes with chemoradiotherapy to cure cancer via metabolically targeting HIF‐1 in a novel triple‐negative glioblastoma mouse model

Abstract: The standard care of glioblastoma multiforme (GBM), which is surgery followed by temozolomide concurrent radiotherapy (RT/TMZ), confers limited survival benefit for patients. 1 Additionally, current animal models do not faithfully recapitulate human GBM features, impeding animal-to-human translation. 2 Here, we developed and characterized a novel orthotopic murine GBM model, in which we tested the efficacy of the RT/TMZ supplemented with mannose (RT/TMZ/Man). Following the optimized protocol illustrated in Fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…For example, it is necessary to calculate the ideal dose of mannose treatment for human inflammation, determine how mannose increases FAO in CD4+ T cells, and whether or not mannose can affect functions of CD8 + T cell and other immune cells. Moreover, since it was also reported that mannose treatment could enhance cancer chemokine therapy ( 52 , 53 ), whether mannose mediated immune responses are involved during this process is totally unknown. Nevertheless, although there are still a number of key questions need to be figured out, the great therapeutic promise of mannose treatment has been disclosed.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…For example, it is necessary to calculate the ideal dose of mannose treatment for human inflammation, determine how mannose increases FAO in CD4+ T cells, and whether or not mannose can affect functions of CD8 + T cell and other immune cells. Moreover, since it was also reported that mannose treatment could enhance cancer chemokine therapy ( 52 , 53 ), whether mannose mediated immune responses are involved during this process is totally unknown. Nevertheless, although there are still a number of key questions need to be figured out, the great therapeutic promise of mannose treatment has been disclosed.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Mannose has shown potential therapeutic properties in a variety of cancers. 10 11 12 We found that mannose can inhibit the growth of PCa cells. Furthermore, mannose can regulate metabolic reprogramming of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 81%
“… 13 Recently, mannose was reported to be effective against lung cancer, breast cancer, and osteosarcoma. 28 , 29 , 30 , 31 , 32 Low expression of PMI makes cells more sensitive to the antitumor effect of mannose, and all of these cancers express low levels of PMI. By contrast, leukemia cells express PMI, but it remains unclear how mannose metabolism contributes to their survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%